MEMBANGUN SISTEM DATABASE ALUMNI UNTUK MENDUKUNG KEMAJUAN SEKOLAH DI ERA MODERN MELALUI PROGRAM PENGABDIAN MASYARAKAT - Diki A.; sri wahyuni (Jurnal Abdimas Universitas Insan Pembangunan Indonesia, 2025)
This community service activity aims to develop and implement an alumni database system at SDN 207 Apala as a digital solution in managing alumni data. This digital innovation is expected to facilitate schools in monitoring the development and contribution of alumni more efficiently and in a structured manner. The method used in this study is a qualitative descriptive approach, with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the implementation of this database system increases efficiency in data management, accelerates the process of inputting and updating alumni information, and strengthens the communication network between schools and alumni. However, the challenges faced include limited technological infrastructure and the need for further training for school staff. Overall, this study makes a real contribution to the development of digital innovation in the world of education, especially in terms of alumni data management